2020
DOI: 10.3390/cancers12030731
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Kinase Inhibitors in Cancer: Breakthrough and Challenges of Targeted Therapy

Abstract: Receptor tyrosine kinases (RTKs) are key regulatory signaling proteins governing cancer cell growth and metastasis. During the last two decades, several molecules targeting RTKs were used in oncology as a first or second line therapy in different types of cancer. However, their effectiveness is limited by the appearance of resistance or adverse effects. In this review, we summarize the main features of RTKs and their inhibitors (RTKIs), their current use in oncology, and mechanisms of resistance. We also descr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
254
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 350 publications
(265 citation statements)
references
References 92 publications
3
254
0
8
Order By: Relevance
“…Nevertheless, the efficacy of chemotherapy has been stagnant for many years. In contrast, the development of new and different therapies, such as targeted therapies for tyrosine kinases [2], as well as immunotherapy using immune-checkpoint inhibitors [3], has been an important leap in recent years. Either way, the ultimate goal is to kill tumor cells and protect normal cells.…”
mentioning
confidence: 99%
“…Nevertheless, the efficacy of chemotherapy has been stagnant for many years. In contrast, the development of new and different therapies, such as targeted therapies for tyrosine kinases [2], as well as immunotherapy using immune-checkpoint inhibitors [3], has been an important leap in recent years. Either way, the ultimate goal is to kill tumor cells and protect normal cells.…”
mentioning
confidence: 99%
“…Inhibitors emerged with more than one protein kinase as a target structure [9]. However, these inhibitors are also affected by resistance mechanisms [10].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinical and early clinical studies with single-targeted agents have shown limited antitumor activity in ovarian cancer. Combining two or more therapeutic agents to target tumor cell survival pathways has become a new strategy to treat cancer [ 16 ]. In this study, we found that combined treatment of several FDA-approved targeted drugs—sunitinib, dasatinib, and everolimus—results in simultaneous inhibition of multiple signaling pathways and a better anti-tumor activity than any single treatment.…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical trials with single-targeted agents have shown limited antitumor activity in ovarian cancer, which could be due to compensation by alternative growth/survival pathways. Thus, an emerging strategy for overcoming resistance is to combine inhibitors targeting multiple oncogenic pathways [ 16 ].…”
Section: Introductionmentioning
confidence: 99%